Personal mobile devices and mental health: A double-edged sword? - Bentley, Wessel (Stellenbosch Theological Journal, 2024)
It has been well documented that there is a correlation between the (over) use of social media and the rise of mental health disorders, especially dependency, depression, anxiety, narcissism, and other behaviour- and mood disorders. The use and functionality of personal mobile devices seized the opportunity to offer individualised and personalised therapeutic services such as applications for mindfulness, exercises to manage depression and anxiety and even to facilitate meditative practices (spirituality). One is then left undecided whether the use of personal mobile devices can be counted as a vice or a blessing. This article will explore impact the use of personal mobile devices have on mental health and the question of being human. It does so within the science and religion discourse.